(3GdeaGgje hGdfXQjGJ s - (3UHQjfI(B, (3SjOj UGdMs ((3GdLRGFQ(B:s (3OGQ GdHGMK ddWHGYI hGdfTQ hGdJhRjY(B,s, 2022)
(3JfGhdfG ef NdGd gPG GdcJGH GdYOjO ef GdYfGUQ GdJj JgOa Edi JTQjM eaghe GdbjGOI hGdGMGWI Hg, MjK JJVef gPG GdCNjQ eONdG YGeG Edi GdbjGOI GdGOGQjI, HYOgG JWQbfG Edi egGQGJ GdbjGOI GdGOGQjI, Ke GdbjGOI GdGOGQjI aj Xd HYV GdfXQjGJ HOAG HGdbjGOI GdGOGQjI aj Xd GdeOQSI GdcdGSjcjI , Ke JUhQGJ GdbjGOI GdGOGQjI aj GdacQ GdEOGQj, aGdfXQjGJ GdJbdjOjIddbjGOI GdfXQjGJ GdPGJjI, hHYOgG GdfXQjI GdSdhcjI aj GdbjGOI, Ke GfJbdfG Edi GdfXQjI GdehbajI aj GdbjGOI, dfJMOK Yf GdfXQjI GdhXjajI aj GdbjGOI, hGdfXQjI GdJaGYdjI hGdfXQjI GdJHGOdjI aj GdbjGOI, hcPG JfGhdfG GdCfeGW GdbjGOjI, haj GdNJGe GMWfG HGdbjGOI hGSJQGJjLjI GJNGP GdbQGQ(B.s
(3eQGLY U(B.170s
Keywords: (3GdbjGOI GdGOGQjIs